(untitled) (European Journal of Economics, Finance and Business Development, 2026)
In the global economy, ensuring the profitability of commercial banks is of strategic importance for the continuous functioning of financial intermediation, the sustainable allocation of credit resources to the real sector, and strengthening the stability of the banking system. With sufficient profitability, banks can expand their capital base, diversify risks, introduce innovative financial products, and pursue a competitive interest rate policy, which serves as a driver of economic growth. On the contrary, low profitability increases the risk of limiting credit activity, deteriorating asset quality, and increasing threats to financial stability. Therefore, in the banking practice of countries around the world, ensuring the profitability of commercial banks is considered one of the priority areas of bank management.